Le patrimoine archivistique et documentaire équin de la Manche : constitution et reconstitution ; construction et valorisation des patrimoines et réciproquement - Alain Talon (In Situ)
For historic, geographical, economic reasons, the department of La Manche is one of the most concerned by the history and the heritage about horse. Departmental records office was totally destroyed in 1944. Archives of the « National stud horse » of Saint-Lô, private archives, sound archives, printed matters, iconography are so many supports of a equine and equestrian multi-form heritage. Heritage becomes also a major issue for the restore of collections. The collecting, the archival and documentary management of all the constituent materials of these material and immaterial heritage, his construction are essential logic for the valorization, the knowledge of this area.